2015
DOI: 10.1016/j.vaccine.2015.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Wheeze as an adverse event in pediatric vaccine and drug randomized controlled trials: A systematic review

Abstract: Introduction Wheeze is an important sign indicating a potentially severe adverse event in vaccine and drug trials, particularly in children. However, there are currently no consensus definitions of wheeze or associated respiratory compromise in randomized controlled trials (RCTs). Objective To identify definitions and severity grading scales of wheeze as an adverse event in vaccine and drug RCTs enrolling children <5 years and to determine their diagnostic performance based on sensitivity, specificity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
1
3
0
1
Order By: Relevance
“…A systematic review of pediatric drug and vaccine trials that included wheeze as an adverse event reported that only 26% of the trials provided a definition of wheezing. 32 The strong agreement between the in-person and recorded examinations in this study suggests that digital audio-video recordings may be a reliable means for future trials and multicenter studies to standardize assessment of respiratory findings.…”
Section: Discussionsupporting
confidence: 58%
“…A systematic review of pediatric drug and vaccine trials that included wheeze as an adverse event reported that only 26% of the trials provided a definition of wheezing. 32 The strong agreement between the in-person and recorded examinations in this study suggests that digital audio-video recordings may be a reliable means for future trials and multicenter studies to standardize assessment of respiratory findings.…”
Section: Discussionsupporting
confidence: 58%
“…This scale is envisaged to provide standardized case definitions in reporting new cases and would facilitate research across studies of optimal management strategies and outcomes. Diagnostic certainty levels have been proposed for randomized control trials in other conditions in children such as wheezing, where standardized definitions are lacking [51]. Additionally, standardized reporting could be adapted from international registries such as the international management platform for ChILD [52] or other global registries.…”
Section: Discussionmentioning
confidence: 99%
“…Wheezing is considered to be an important outcome of interest in vaccine safety assessments [19], and there was a specific concern about wheezing after LAIV [17,20,21]. As noted above, LAIV was in use during the seasons our study was conducted 2014–15 and 2015–16).…”
Section: Discussionmentioning
confidence: 99%